Interventional Program on Nurses Practices Regarding Burn Wound Dressing - Yas Khadher Baiez, Widad K Mohammed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Wound management is a crucial aspect of patient care and the nurse often is faced with the question of which approaches to use to provide an environment that supports healing and prevents complications. Important questions include how different types of wounds should be dressed, what method of debridement to use, whether dressings should be changed using sterile versus unsterile technique, and which adjunctive therapies to select under given circumstances, thus the aim of this study is to evaluate the effect of an intervention program on nurse’s practices regarding dressing burn wound. Methodology: A quantitative (one pre experimental) design had been adapted through the present study with the application of pre- post-test approach during the period of 17th October, 2020 to 20th March, 2022. A non-probability (convenient) sample of 24 nurses who work at burns and plastic surgery center at Azady teaching hospital. The interventional program and study instrument is designed based on of the nurse’s practice assessment need, review of literature, scientific lecturer and previous study. The content of the program and instrument are evaluated by 16 experts in different field and the reliability of instrument is determined through the use of test and retest, measurement of effectiveness for nursing education program carried out through (24) items concerning clinical guidelines regarding burn management. The analysis of data is performed through the application of descriptive statistic as well as inferential statistic by using statistical package of social science version 22. Result: shows that vast majority of the sample were male, 30-39 years old, high school graduate, less than 5 years of experience. Most of the samples participate in burn courses, one course in number, their courses inside Iraq. Comparisons significant at P<0.01 was high regarding initial survey’s, secondary survey’s, total body surface, initial assessment of the depth of the burn wounds, burn wounds, removing dead tissue and cleaning the burn’s. Conclusion: study conclude that Nurses’ Practice improvements due to applying of the proposed interventional program with relative to demographical characteristics. The study recommends that nurses practice toward burn management should be updated periodically as well as encourage nurses to participate in sessions, conferences and seminar related to care of burn